Progress in the Chemistry of Organic Natural Products 109 - Kinghorn, A. Douglas; Falk, Heinz; Gibbons, Simon; Kobayashi, Jun'ichi.; Asakawa, Yoshinori; Liu, Ji-Kai.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume comprises three reviews. The first describes isolation, structure determination, syntheses, and biochemistry of the low molecular weight compounds of the secretion of exocrine glands of termies with emphasis to pheromones and defensive compounds. The second review describes recent studies on isolation and structure elucidation of bioactive compounds involved in the life cycle and determination of the molecular mechanisms of the developmental events observed in higher plants. The third contribution reports on the current body of knowledge of African propolis, with a particular emphasis on its chemistry and biological activity. .
Chemistry of the Secondary Metabolites of Termites -- Bioactive Compounds in the Life Cycle of Higher Plants -- Chemical Diversity and Biological Activity of African Propolis.
Keywords: Chemistry, Organic; Pharmaceutical chemistry; Medicinal chemistry; Organic Chemistry; Pharmaceutics; Medicinal Chemistry